MELAYU PERSEMBAHAN DANCE: THE MEANING OF FORM AND MOVEMENT AS LOCAL WISDOM IN RANAI CITY, NATUNA REGENCY - Mega Cantik Putri Aditya (Jurnal Scientia, 2023)
The purpose of this study was to determine the elements of motion, structure and meaning in the Malay Present dance in the city of Ranai, Natuna Regency. This dance as a dance that tends to always be performed when guests of honor arrive in the city of Ranai, every element and structure in this dance movement has a meaning and purpose that reflects the happiness of the people in welcoming guests with gentleness and paying attention to the courtesy that appears in every movement and costume used characterized by ethnic Malay society. The approach used in this study is an ethnochoreological approach that can discuss the Malay Sacrifice Dance textually and contextually. Presentation of data in a descriptive qualitative manner is felt to be able to describe the results of this study clearly and straightforwardly. The research method used in this study is a qualitative method with data collection techniques namely, observation, interviews, literature study, and documentation. The results of this study can be interpreted that the Malay Offering Dance is a welcoming dance. There are 11 variations of the Malay Offering dance movements consisting of the initial movements of the uphold tepak variety to the opening greeting variety, the betel nut blending movement to the end of the beni sari variety, the closing greeting variety of movements. This dance is danced by female dancers and the number is odd. The meaning of the motion of the Malay Offering Dance in general describes the grace and beauty of the women on the Natuna coast. This dance tells about the activities of women in welcoming guests, serving betel and opening the way for distant guests who have come to visit the area. The meaning in this tarekat means honor, gentleness and courtesy of the Malay community.